Supplementary exam tracking system (SETS) - Heng, Jooi Huang (2007)
This project – Supplementary Exam Tracking System (SETS) is aim to develop a platform to collaborate supplementary exam affairs among students, Registrar and Assistant Registrars (ARs) from exam department, and Bursar and Assistant Bursars (ABs) from financial department within the six campuses at Tunku Abdul Rahman College (TARC). The SETS is a web-based application that developed using ASP.NET programming language. Besides that, Rational Unified Process (RUP) that advocates Object-Oriented Methodology (OOM) in system implementation and Unified Modeling Language (UML) for diagram modeling are selected as a guide in developing the proposed SETS system. Through the SETS, students from different campuses can register their resit or repeat papers online and receive their reminded message if they forget or have not settled their payment. In addition, SETS is able to reduce the workload of Registrar and Assistant Registrars (ARs) from exam department whose jobs are multitasking in nature. Overall, the proposed SETS system is significant to TARC as it can further enhance the college efficiency and effectiveness in delivering the customer services to students as well as increase the reputation of TARC.